Role of the mass media in Malaysia's general elections / Dr. Bukhory Ismail and Dr. Sankaran Ramanathan - Ismail, Bukhory (Dr.); Ramanathan, Sankaran (Dr.) (Faculty of Communication and Media Studies (FCMS), 2004)
Malaysia, a federation of 13 states, formerly under British rule or control has held periodic elections since its creation in 1957. As with any democracy, the media have played an important role in the pre-election build-up as well as during the two-week campaign periods. The role of the media in the political process has become even more significant in the eighties, with the increasing levels of sophistication of the electorate brought about by greater education, progress and development as well as the development, increasing sophistication and diversification of the mass media themselves.